(3CLhHI CSFdI aj GdYbGFO fXekG hfKQkGs - (3eMeO Hf YHO GdHGbj GdRQbGfj GdeGdcj , CHh YHO Gddg,J (B1122 (3g` s ((3jhSa GdJdi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai CeG HYO abO LGAfi HYV GdfGS HCSFdI LeYgG ef CeGcf TJi hLYdgG fXekG acJHJ YdjgG eG jSQg Gddg JYGdi ef aVdg s
(3BNQgG (B:s
(3hPcQ GdbSWdGfi Yf GHf bJjHI ai GdeYGQa Cf BOe de jcf dg dMjI hGdChd CUM GfJgi hbO JbOe Cf gPG ef GdESQGFjdjGJ hdG jKHJ hgPG eG jSQg Gddg JYGdi ef GdcJGHI Ydi gPg GdCSFdI ddYHO GdabjQ eMeO Hf YHO GdHGbi GdRQbGfi GdeGdci s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi UaMI GdYfhGf aGFOJjfs
(3ai Chd GdeNWhW hQbJGf cJH Ydi ChdgeG gPG cJGH GdRgQ GdaGFM ai hUa ef JfRg Yf GdPfhH hGdbHGFM s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds